Pengembangan Video Pembelajaran Berbasis Lingkungan untuk Meningkatkan Literasi Siswa SMP di Kelas VIII - Linda Santi Rozana Mendrofa; Ester Julian Mendrofa; Linda Tri Utami Zendrato; Yanida Buulolo (Departement of Mathematics Education, 2023)
This research was conducted to create an environment-based learning video that would help junior high school students in their literacy skills. In order to increase the literacy of junior high school students, this research aims to make environmental education films as cutting-edge media. Research and development techniques used in this study (Research and Development). To collect data from different people or groups, this study uses a questionnaire instrument consisting of a number of written questions. The results showed that when measured using environmental literacy indicators, students' environmental literacy levels had different average values, with cognitive skills of 80% (good criteria), environmental awareness of 70.67% (good criteria), and responsible behavior. environmental responsibility. of 89.22% (very good criteria).